The dynamic economic landscape of Bengkulu: A comprehensive analysis and its implications for sustainable growth across sectors - Arsyah, Teguh Dwi; Pakri, Pakri (Journal of Economics and Business Letters, 2023)
This research presents a comprehensive examination of the economic climate of Bengkulu, a province on the southwest coast of Sumatra, Indonesia. Utilizing a mixed-methods approach, this study combined qualitative and quantitative data collected from a purposive sample of 135 participants, including local business owners, government officials, economic analysts, and residents. This study investigates various economic indicators such as income levels, employment statistics, and sectoral contributions to the regional economy. Employing a hypothetical regression analysis, this study explores the connections between sectoral contributions, employment rates, growth rates, and consumer spending in key sectors such as agriculture, services, mining, and retail and their impact on regional Gross Domestic Product (GDP) growth. The findings reveal a dynamic economic landscape with significant growth observed in certain sectors while also highlighting challenges such as economic inequality and the need for diversified economic strategies. This study not only offers insights into the current economic status and trends in Bengkulu, but also provides critical information for policy-making and strategic planning aimed at promoting sustainable and inclusive economic growth in the region.